Comparison of Electronic Mail with Other Modes of Communication among College Lecturers - Rani, Sunita (INTI Publishing House Sdn Bhd, 2005)
The rapid growth of global telecommunication networks, and in particular the Internet, has placed emphasis on the electronic mail as a mode of communication, entertainment, educational tool, and personal correspondence medium. Emphasis should be given in colleges to understand the nature of its use and its implementation among lecturers since they are directly involved in the transmission of teaching and learning within the college in order to assess the implementation of e-mail in INTl College Malaysia, a survey was done to seek lecturers’ responses to its use and to compare its use in comparison to other modes of human communication. Results showed that the majority (52.6 to 79.4 %, from the five Schools) of lecturers reported that e-mails were an effective and efficient means of communication. Respondents expressed satisfaction with the e-mail system, as 55.1 % reported that e-mails increased their work productivity. E-mail was the most popular mode, followed by telephone and face-to face (FTF) communication. Other modes of human communication include written memos, group meetings, and letters, voice mail on the hand-phones or desk phones, newsletters, teleconferencing and facsimile transmission. Only 40.6% of lecturers agreed that e-mail was replacing FTF communication. Overall, 59.3% of lecturers agreed or strongly agreed that people tend to receive immediate feedback in meetings compared with using e-mails. The majority (77.3%) of lecturers agreed that certain messages should be given verbally, not by e-mail.